Human dignity: Is there a place for it in planning? (Transactions of the Association of European Schools of Planning, 2020)
Although human dignity has caught the attention of scholars in many different fields, planners remain unresponsive. Three reasons may be given for planners’ neglect of human dignity: (1)  so far, nobody has inspired planners to cherish human dignity as a planning value or goal; (2)  planners respect and protect human dignity, but do not use the term; (3)  planners distrust values that are not too complex for laypersons. Two cases illustrate the possible consequences of ‘planning for dignity’ – the case of the knitting ladies of Blikkiesdorp (Cape Town), and the poor door controversy of 2014. The most important conclusions are that planners, in order to align their plans with human dignity (or ubuntu), must co-produce their selves within local communities affected by their plans. Moreover, planners must recognize the tension that exists between social justice and human dignity: A plan that is socially just can still be humiliating.
Keywords: Human dignity; housing; poor doors controvers; social justice; spatial injustice; planning theory; ubuntu